2018
DOI: 10.7287/peerj.preprints.26598
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High cell density cultivation of Escherichia coli DH5α in shake flasks with a new formulated medium

Abstract: High cell density cultivation of Escherichia coli DH5α in shake flasks with a new formulated mediumHigh cell density cultivation necessitates cell division and biomass formation, the mechanisms of which remain poorly understood, especially from the cellular energetics perspective. Specifically, the sensing of energy abundance and the channelling of nutritional energy into biomass formation and cell maintenance remains enigmatic at the sensory, effector and decision levels. Thus, optimization of cell growth rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…This suggested that metabolism of 6 g/L glucose could have generated unique metabolites that nonspecifically adsorbed to the cell surface, or there was physiological adaptation to growth in LB Lennox (buffered) medium with 6 g/L glucose supplementation that resulted in changes to the cell surface characteristics. Growth of E. coli DH5α in Tryptic Soy Broth, LB Lennox and formulated medium 3 resulted in zeta potential-pH profiles with the same pHzpc, but the profiles exhibited differences in the pH range from 4 to 12 (Figure 3). Specifically, within the pH range from 4 to 12, the zeta potential-pH profile of E. coli DH5α grown in Tryptic Soy Broth was more negatively charged compared to that of cells grown in formulated medium.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This suggested that metabolism of 6 g/L glucose could have generated unique metabolites that nonspecifically adsorbed to the cell surface, or there was physiological adaptation to growth in LB Lennox (buffered) medium with 6 g/L glucose supplementation that resulted in changes to the cell surface characteristics. Growth of E. coli DH5α in Tryptic Soy Broth, LB Lennox and formulated medium 3 resulted in zeta potential-pH profiles with the same pHzpc, but the profiles exhibited differences in the pH range from 4 to 12 (Figure 3). Specifically, within the pH range from 4 to 12, the zeta potential-pH profile of E. coli DH5α grown in Tryptic Soy Broth was more negatively charged compared to that of cells grown in formulated medium.…”
Section: Resultsmentioning
confidence: 99%
“…Buffer systems are commonly incorporated into medium formulation to help the culture broth maintain a stable pH around neutral to provide a conducive environment for biomass formation. 3 One such buffer system is K2HPO4 and KH2PO4. 3 Using the potassium hydrogen phosphate buffer system with 89 mM of phosphate, LB Lennox (buffered) growth medium was effective in buffering pH changes that arise due to the secretion of various metabolites by E. coli DH5α during growth in the medium.…”
Section: Measurement Of Zeta Potentialmentioning
confidence: 99%
See 1 more Smart Citation